CORRELATION BETWEEN RESTLESS LEGS SYNDROME AND MIGRAINE HEADACHES - Ismati Z.O; Djurabekova A.T. (Scholar Express Journals, 2025)
Restless Legs Syndrome (RLS) and migraine headaches represent two distinct yet potentially interconnected neurological disorders that significantly impact patients' quality of life. RLS, also known as Willis-Ekbom disease, is characterized by an irresistible urge to move the legs, typically accompanied by uncomfortable sensations that worsen during periods of rest and improve with movement. These symptoms predominantly occur in the evening or nighttime hours, often leading to sleep disturbances and daytime fatigue.
Keywords: Restless legs syndrome; migraine; dopaminergic connection